Issues in Chinese Nepali Sound Translation: An Equivalence Based Dualistic Approach - Dharma Dev Bhatta; Yu Xinya (Journal of English Education and Teaching, 2021)
This paper sheds light on the phonological issues of Chinese-named entities transliterated into Nepali in contrast to the Source language phonology, Hàny? P?ny?n (pinyin) and the target language phonology. We compared 500 transliterated nouns, related their pronunciation to source language employing speaker and listener oriented experiment on phonological similarity and found out that the prevailed sound translation approaches are strictly inclined to pinyin, where the preservation of the source language phonological units and their nativization in target language orthography, the priority over phonological equivalence are completely neglected and the prevalent issues like phonological gaps, inconsistencies, mis-syllabification etc. aroused. We purpose phonological based Dualistic Equivalence Approach (hybrid transliteration approach)based on Nepali Chinese bilinguals’ perceptual similarity to address the existing issues mainly where the monotonous sound alignment in between source language, pinyin and target language breaks down.